2009
DOI: 10.3897/biorisk.3.14
|View full text |Cite
|
Sign up to set email alerts
|

A summary of birds recorded in the marshes of southern Iraq, 2005–-2008

Abstract: Th e marshlands of Lower Mesopotamia witnessed severe draining programs during late 1980s and early 2000s, which turned vast areas of the former water body into desert areas. New fi eld surveys of birds and their habitats in the marshes of southern Iraq were launched in 2005 through a national and international partnership of non-government organizations, ministries and donor agencies. Th is has resulted in the collection and collation of new data on the status, distribution and habitat requirements of birds a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 0 publications
0
45
0
Order By: Relevance
“…For this reason, there is a clear need to undertake further, intensive surveys in the other two Mesopotamian marshes to provide accurate, up-to-date information. Recent national water and biodiversity strategies have indicated that it is no longer appropriate to consider all three marshes as one conservation unit, as the connections between the water bodies have severely declined due to extreme water scarcity [10]. As such, there is an urgent need to develop management plans for each of the three Mesopotamian marshes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, there is a clear need to undertake further, intensive surveys in the other two Mesopotamian marshes to provide accurate, up-to-date information. Recent national water and biodiversity strategies have indicated that it is no longer appropriate to consider all three marshes as one conservation unit, as the connections between the water bodies have severely declined due to extreme water scarcity [10]. As such, there is an urgent need to develop management plans for each of the three Mesopotamian marshes.…”
Section: Discussionmentioning
confidence: 99%
“…Parts of the CM were reflooded and restored in 2003 using the River Euphrates water to feed the CM directly, resulting in a huge reverse migration of both local people and bird species [9,10]. Concomitantly, there was a change in governmental attitudes and NGOs toward wildlife and the value of birds, especially regarding the maintenance of healthy ecosystem functioning [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mesopotamian Marshes have played a vital role as a wintering habitat for migratory birds, supported globally threatened and endangered species, and sustained a productive shrimp and finfish fishery (UNEP 2001). Between 1 and 10 million migratory waterfowl and shorebirds have made their way in the winter from Siberian nesting grounds along the flyway to the Marshes and northern Africa (Scott 1995, Shattersfield et al 1998, Salim et al 2009, Porter and Aspinall 2010, Ararat et al 2012). There are 22 species of globally endangered species and 66 at-risk avian species in the Marshes (UNAMI 2011).…”
Section: Marsh Ecosystem Services and Biodiversitymentioning
confidence: 99%
“…During May 2004-May 2005, a total of six raptor species were recorded in three restored marshes (Huwayzah, Suq Shuyukh, and East-Hammar marshes) (Abed, 2007); the recorded species were Western Marsh Harrier, Hen Harrier, Eurasian Sparrowhawk, Greater Spotted Eagle, Steppe Eagle, and Golden Eagle Aquila chrysaetos (Linnaeus, 1758). Salim et al (2009) listed nine raptor species among the avifauna of lower Mesopotamian marshlands of southern Iraq that observed in [2005][2006][2007][2008]; the listed species were Common Kestrel, Western Marsh Harrier, Black-winged Kite Elanus caeruleus (Desfontaines, 1789), Long-legged Buzzard, Hen Harrier, Eurasian Sparrowhawk, Greater Spotted Eagle, Steppe Eagle, and Asian Imperial Eagle.…”
Section: Introductionmentioning
confidence: 99%